Feline chronic gingivostomatitis in a nine-year-old neutered male Persian cat mix a case report - Monfero-Mariño, Anselma; George Anthony, James Mudie (2022)
A nine-year-old neutered male Persian cat mix was presented for halitosis, blood-tinged saliva, poor appetite, and weight loss. The cat was diagnosed with Feline Chronic Gingivostomatitis (FCGS), a disease characterized by painful swelling of caudal oral tissues of unknown aetiology. Diagnosis was determined through detailed oral examination, oral radiography, and histopathology. Oral radiography demonstrated periodontitis with horizontal bone loss, tooth resorption, and retained tooth roots. Tests for Feline Immuno Deficiency Virus (FIV) and Feline Calicivirus (FCV) were administered to determine if they play a role in FCGS of which yielded low positive and negative results, respectively. Histopathology of caudal mucosal tissues showed subacute to moderate lymphocytic mucositis, undertaken to rule out neoplasia. Tissue swab isolated Escherichia coli. Since the pathogenesis of FCGS is multifactorial and inciting causes like periodontitis, tooth resorption, and retained roots were present in this case, full mouth dental extractions were performed. The gradual resolution of inflammation of caudal mucosa and palatoglossal folds were observed post operatively on days 6, 31, 67, 92, and 948. Full mouth extractions were completed in four visits using total intravenous anaesthesia (TIVA) and local blocks. Medical therapy using 1-TDC, 0.12% chlorhexidine oral spray, meloxicam, and marbofloxacin was also done.
Keywords: Veterinary dentistry; Cat diseases; Oral hygiene